Soluzioni informatiche innovative a supporto della Decostruzione Selettiva - Bottaro, Antonio (GEOmedia, 2017)
Building processes and designs have to be renewed to take account of environmental concerns. To reduce the impact of construction projects on the environment, the design needs to take the issue of building materials into consideration. Public administrations need suitable tools for the calculation and the control of reused or disposed materials. Innovative IT tools should handle the digital processing of materials throughout the project, supporting new project requirements such as: Design for Deconstruction, Design for Recycling and Design for Waste.